Impact of clinical pathways on enhancing compliance with evidence-based therapies for Heart failure with reduced ejection fraction–A retrospective cohort study - Naga Sasidhar Kanaparthy; Stephen Possick; Wei Teng; Christopher Maulion; Nancy Kim (PLoS ONE, 2025)
Background Heart failure (HF) mortality is rising despite robust evidence-based guidelines. Hospitalization presents an opportune time to optimize care. Inpatient care pathways (CP) embedded in the electronic health record (EHR) can enhance adherence to guidelines by providing real-time decision support. Objective To measure the impact of the heart failure reduced ejection fraction (HFrEF) CP on early diuretic use, goal-directed medical therapy (GDMT), and referral to comprehensive HF management (CHFM) on discharge. Methods A HFrEF CP embedded into the EHR was built by multidisciplinary providers across a large academic medical center. Providers could place orders and document notes directly from the pathway. We conducted a retrospective cohort study of all the HF hospitalizations two years after pathway implementation and further limited the cohort to those with ejection fraction (EF) ≤ 40%. We compared rates of early diuretic use, GDMT, and referral to CHFM between cohorts defined by pathway use. Results 1,639 patients contributed 2,062 hospitalizations. The pathway was opened in 362 (17.6%) hospitalizations. There were no significant clinical or sociodemographic differences between groups. Bivariate analyses revealed more GDMT (χ2 (1) = 3.651, p = 0.056); while multivariable analysis showed more early diuretics (OR = 1.58, 95% CI 1.19, 2.09, p = 0.002) and referrals to CHFM (OR = 3.24, 95% CI 2.54, 4.12, p < 0.001) in the pathway group. Conclusion Despite low utilization, pathway use was associated with more early diuretics and referrals to CHFM with a trend toward more GDMT on discharge. CPs are a feasible strategy to optimize care for hospitalized HF patients.